The Effect of Emotion Regulation on Academic Stress among Guidance and Counseling Study Program Students at Universitas Jambi - Khairunnisa, Nadjwa; Elfira, Ninil; Sarman, Freddi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study on the effect of emotion regulation on academic stress among university students is grounded in the fact that students face high academic demands while simultaneously undergoing a transitional phase into adulthood, which may trigger negative emotions. During this period, students may experience stress due to difficulties in adapting to these changes. In the educational context, students frequently encounter academic pressures, characterized by heavy coursework, rigorous examinations, and a competitive environment. These pressures can lead to negative impacts known as academic stress. One of the determining factors of academic stress is emotion regulation; therefore, students are required to enhance their emotional regulation abilities. Effective emotion regulation enables students to think more carefully and act objectively. This study employed a quantitative method with an ex post facto approach. The sample consisted of 182 students selected using simple random sampling. The instruments used were an emotion regulation questionnaire comprising 38 items and an academic stress questionnaire consisting of 46 items. Data were analyzed using simple regression analysis. The results showed an Asymp. Sig value of 0.200 and an R Square value of 0.381. The regression equation indicates that emotion regulation has a significant effect on academic stress, meaning that as emotion regulation increases, academic stress decreases.